New biological insights into the Middle Triassic capitosaurs from India as deduced from limb bone anatomy and histology. (28th June 2019) - Mukherjee, Debarati; Sengupta, Dhurjati P.; Rakshit, Nibedita
Abstract: Multiple limb bones of different Middle Triassic capitosaurs from India including Cherninia denwai and Paracyclotosaurus crookshanki were examined to reveal differences in palaeobiology and lifestyle adaptations. Limb bone anatomy of Cherninia is characterized by distinct torsion and its absence in the fore and hindlimb bones, respectively. Substantial torsion is seen in all the limb bones of P. crookshanki . Woven fibred bone tissue, a very rapidly deposited tissue mostly seen in the embryos and very young individuals of higher vertebrates, is reported for the first time in a juvenile temnospondyl. Predominance of incipient fibrolamellar bone tissue is seen in a large bodied Middle Triassic temnospondyl suggesting that such tissues in non‐amniotes helped in achieving large body sizes rapidly. Highly vascularized woven fibred bone tissue in the early ontogeny, transforming to a more stable incipient fibrolamellar bone tissue associated with growth marks later in ontogeny characterizes C. denwai . This suggests rapid sustained growth slowed down and became punctuated later in ontogeny. A continuous slow growth throughout ontogeny is suggested for P. crookshanki as parallel fibred bone and azonal lamellar bone tissue are seen in all the examined limb bones. The growth of C. denwai and P. crookshanki had variable susceptibility to seasonal fluctuations. The onset of sexual maturity was at 55% adult size for Cherninia as implied from the change in tissue type. Cherninia inhabited the bottom of the water column and acted as a passive benthic predator whereas Paracyclotosaurus was a shallow water predator that retained a high level of terrestriality.